Aerobic Exercise Training Prevents Heart Failure-Induced Skeletal Muscle Atrophy by Anti-Catabolic, but Not Anabolic Actions - Souza, Rodrigo W. A. [UNESP]; Piedade, Warlen P. [UNESP]; Soares, Luana C. [UNESP]; Souza, Paula A. T. [UNESP]; Aguiar, Andreo F.; Vechetti-Junior, Ivan J. [UNESP]; Campos, Dijon H. S. [UNESP]; Fernandes, Ana Angelica Henrique [UNESP]; Okoshi, Katashi [UNESP]; Carvalho, Robson F. [UNESP]; Cicogna, Antonio Carlos [UNESP]; Dal-Pai-Silva, Maeli [UNESP] (Public Library Science, 2014)
Background: Heart failure (HF) is associated with cachexia and consequent exercise intolerance. Given the beneficial effects of aerobic exercise training (ET) in HF, the aim of this study was to determine if the ET performed during the transition from cardiac dysfunction to HF would alter the expression of anabolic and catabolic factors, thus preventing skeletal muscle wasting.Methods and Results: We employed ascending aortic stenosis (AS) inducing HF in Wistar male rats. Controls were sham-operated animals. At 18 weeks after surgery, rats with cardiac dysfunction were randomized to 10 weeks of aerobic ET (ASET) or to an untrained group (AS-UN). At 28 weeks, the AS-UN group presented HF signs in conjunction with high TNF-alpha serum levels; soleus and plantaris muscle atrophy; and an increase in the expression of TNF-alpha, NF kappa B (p65), MAFbx, MuRF1, FoxO1, and myostatin catabolic factors. However, in the AS-ET group, the deterioration of cardiac function was prevented, as well as muscle wasting, and the atrophy promoters were decreased. Interestingly, changes in anabolic factor expression (IGF-I, AKT, and mTOR) were not observed. Nevertheless, in the plantaris muscle, ET maintained high PGC1 alpha levels.Conclusions: Thus, the ET capability to attenuate cardiac function during the transition from cardiac dysfunction to HF was accompanied by a prevention of skeletal muscle atrophy that did not occur via an increase in anabolic factors, but through anti-catabolic activity, presumably caused by PGC1a action. These findings indicate the therapeutic potential of aerobic ET to block HF-induced muscle atrophy by counteracting the increased catabolic state.